A generalized thermophysical model for materials from molecular clusters to bulk crystals - Amirul Edham, Roslee; Nik Abdullah, Nik Mohamed; Thamburaja, Prakash; Jose, Rajan (Elsevier B.V., 2023)
Evolution of properties of bulk materials from its molecular clusters has been a relatively unexplored topic. In this article, we present a generalized model for total thermal energy and heat capacity of solids by considering that a bulk solid is evolved from zero-dimensional molecular clusters through one-dimensional wires and two-dimensionalquantum sheets. The basic difference among these structures is shown to be the phonon density of states, which is continuous (unconfined) in a bulk solid, whereas it is confined in one, two, and three dimensions in QSs, QWs, and QDs, respectively. Considering a semi-empirically derived phonon density of states and the total unconfined and quantum confined dimensions in these structures, we arrived at a generalized equation. The generalized equation fits well to many experimental heat capacities including palladium and nickel nanoparticles, single-walled carbon nanotubes, and cadmium selenide quantum dots with high degree of accuracy (R2 > 0.99). This close agreement between experiments and the generalized equation derived herewith provide promising directions to understand the evolution of bulk properties of materials.